ESTABLISHMENT OF A PHEASANT (PHASIANUS COLCHICUS) SPERMATOGO-NIAL VEGETATIVE CELL LINE FOR THE ASSEMBLY OF INTERSPECIES GERMLINE CHIMERAS - PROF. MARTHAN, PROF. HWISHART (International Journal of Multidisciplinary Research and Studies, 2021)
Background Spermatogonial stem cells (SSCs) are important for the assembly of interspecies germ line chimeras. The interspecies cell transfer technique has been suggested as some way to conserve endangered birds. Our objective was to develop a way for restoring endangered birds by developing interspecies germ line chimeras between pheasant (Phasianus colchicus) and chicken (Gallus gallus) with SSCs. Results SSCs were isolated from the surgically removed testis of a pheasant. Growth conditions for pheasant SSCs were established by co-culturing STO (SIM mouse embryo-derived thioguanine and ouabain resistant) cells and pheasant SSCs. The colony-forming cells divided and proliferated stably to yield a longtime SSC line. Pheasant SSCs showed strong reactivity for the GDNF family receptor alpha1 (GFRα1) marker. Finally, the assembly of germ line chimeras was attempted by transferring pheasant SSCs into recipient embryos. Although final embryo survival was 5.6% (20/354), the initial survival rate was 88% (312/354). to live the percent transfer of donor SSC to gonads, the pheasant SSCs were labeled with PKH 26 dye. We observed 30% donor cells and 9.48% c-kit/CD117-positive cells within the gonads of recipient chickens. Donor SSCs were thus stably engrafted within the recipient gonads. Conclusions This study showed that SSCs will be used as a tool for the conservation of endangered birds and also the production of germ line chimeras. Our findings yield insights into how we may use the pheasant spermatogonial vegetative cell line for efficient production of interspecies germ line chimeras and ultimately, to the restoration of endangered birds.